Integrated Social Policy from Concept to Practice : Report II (United Nations, 2008)
In much of the Arab region, economic development is not guaranteeing social benefits. Poverty and unemployment continue to plague many countries, and basic social services, including health and education, are inequitable, inadequate or absent. In this report, which forms part of the second phase of the Integrated Social Policy Project launched by ESCWA in 2002 and which has been peer-reviewed and extensively discussed in expert group debates, ESCWA attempts to provide concrete entry points to address the developmental needs and goals of the region in a manner that ensures social equity and human rights? The report offers policymakers, civil society organizations, regional and international development agencies and other stakeholders in the region guidelines and suggestions for institutionalizing an integrated social policy approach that embodies the totality of social interventions and takes into consideration social equity and human rights in devising plans for social change and development.